Characterization of the caretaker of elderly people attending the CLASS Pillcomarca-2011 - Veramendi Villavicencios, Nancy (2017)
Objective. To determine the characterization of the caretaker of the elderly person. Methods. They conducted a simple descriptive study with 60 caregivers, from CLAS Pillcomarca, Pillcomarca district, department of Huanuco, during the period 2011. In the collection of data used different scales and psychological questionnaires. For the inferential analysis of the results was used Chi-square test for comparison of a single sample. Results. 65.0% of caregivers of older adults were children, 78.3% were female, 63.3% of Catholic religion, 58.3% were homemakers, 80.0% had low incomes and over 6 years of care, 61.7% had mild depression, 15.0% fatigue and sleep disturbances, irritability, and 86.7% reported 71.7% had low back problems. These results were statistically significant (P ≤ 0.05). Conclusions. The daughters, the Catholic faith, a homemaker, low income, more than 6 years of care, and the presence of mild depression, fatigue and sleep disturbances, irritability and back pain were most important characteristics of caregivers of older adults.